The expanse. Season six [videorecording (DVD)] - Fergus, Mark; Ostby, Hawk (Universal, 2023)
Holden and the crew of the Rocinante fight alongside the Combined Fleet of Earth and Mars to protect the Inner Planets from Marco Inaros and his Free Navy's campaign of death and destruction. Meanwhile, on a distant planet beyond the Rings, a new power rises. Episodes include: Strange Dogs; Azure Dragon; Force Projection; Redoubt; Why We Fight; Babylon's Ashes.